Factors of students' reading lateness - Aini, Nurul (LADU: Journal of Languages and Education, 2021)
Background: Â Reading is still considered trivial by Indonesian, especially parents of students. Purpose: This research aims to find out what are the factors that cause students to be late in reading.Design and methods: This research use a type of literature review research method. researchers seek information about research from several relevant journals and articles, read and record information obtained from data sources and compile research articles from data and information that has been collected. The author will discuss the factors of delay in learning to read in studentsResults: Some of the factors that students to be late in reading are: 1) external factors that can cause reading difficulties are family and school conditions and 2) internal factors that are found in the individual himself